Les enfants du capitaine Grant - Verne, Jules, 1828-1905 (Salt Lake City, UT : Project Gutenberg, 2004)
"Les enfants du capitaine Grant" by Jules Verne is an adventure novel published in 1868. When Lord Glenarvan's crew discovers a mysterious message in a bottle found inside a shark, they learn that Captain Grant and two companions have been shipwrecked. The message reveals their latitude but not their longitude. Glenarvan organizes an expedition with Grant's children to search along the thirty-seventh parallel, circumnavigating the globe through South America and Australia, facing treacherous landscapes, dangerous wildlife, and unexpected betrayals in their quest to find the missing captain. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/In_Search_of_the_Castaways Wikipedia page about this book: https://fr.wikipedia.org/wiki/Les_Enfants_du_capitaine_Grant
Release date is 2004-11-26
Produced by Ebooks libres et gratuits at http://www.ebooksgratuits.com
Keywords: Australia -- Fiction; Ship captains -- Fiction; South America -- Fiction; Voyages and travels -- Fiction; Seafaring life -- Fiction; Castaways -- Fiction; Ocean travel -- Fiction; New Zealand -- Fiction